Proof-of-concept for removing micropollutants through a combination of sub-atmospheric-pressure non-thermal plasma and hydrodynamic (super)cavitation - Mojca Zupanc; Gregor Primc; Matevž Dular; Martin Petkovšek; Robert Roškar; Rok Zaplotnik; Jurij Trontelj (Ultrasonics Sonochemistry)
The persistence and toxicity of hazardous pollutants present in wastewater effluents require the development of efficient and sustainable treatment methods to protect water resources. In this study, the efficacy and efficiency of a novel combination of two advanced oxidation processes – sub-atmospheric-pressure plasma and hydrodynamic cavitation – were systematically tested for the removal of valsartan (VAL), sulfamethoxazole, trimethoprim, naproxen, diclofenac (DF), tramadol, propyphenazone, carbamazepine, 17β-estradiol (E2) and bisphenol A (BPA). The results show that both sample temperature and plasma power play a role and the highest removal, from 29–99 %, was achieved at 25 ℃ and 53 W of plasma power. E2, BPA, DF, and VAL were removed to the highest degree. These results are particularly important in the case of E2 and BPA, whose harmful environmental effects may start to occur already at sub-ng/L to µg/L levels. The differences in the removals obtained depend strongly on the physicochemical properties, and the compounds with the highest logKOW were removed to the highest extent. The energy yield, in terms of plasma power, was between 1 and 26 mg/kWh under optimal experimental conditions. Our results show that the novel plasma-cavitation treatment shows potential that could prove valuable for upcoming regulatory requirements.